Significance of B cell subsets in peripheral blood of syphilis patients - Jun ZHANG; Tao HUANG; Wen-tao CHEN; Xiao-li WAN; Jie-yi YANG; Yao-hua XUE; Wu-jian KE; Xiao-hui ZHANG; Liu-yuan WANG; He-ping ZHENG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2019)
Objective: To determine the subpopulations of B cells in peripheral blood of syphilis patients, and its association with syphilis status. Methods: Peripheral blood was taken from untreated patients with syphilis (18 cases), syphilitic serofast patients (14 cases), serological cure patients (19 cases) and normal controls (16 cases). Mature and regulatory B cells were detected by flow cytometry. Results: Compared with normal controls, the proportions of CD19+ CD24hi CD38hi regulatory B cells were significantly lower in syphilis patients (versus normal controls, untreated: t=2.10, P<0.05; serofast: t=4.04, P<0.05; serological cure: t=2.43, P<0.05). Moreover, the frequencies of mature CD19+ CD24int CD38int B cells were significantly lower in both untreated and serofast patients than in normal controls (t=3.04, P<0.01 for untreated; t=4.44, P<0.01 for serofast). In contrast, proportions of mature CD19+ CD24int CD38int B cells in peripheral blood were comparable between serological cure and normal controls (t=1.03, P>0.05). Conclusions: The ratio of B cell subsets is different between syphilis patient and normal controls. Proportion of mature B cells in serofast patients is abnormal, possibly due to serofast.